Capabilities for data-driven innovation in B2B industrial companies - Eriksson Taina; Heikkilä Marikka (Elsevier, 2025)
Industrial companies are increasingly interested in innovating through data to develop solutions for customers' current and future needs. This study examines organizational capabilities for data-driven innovation (DDI) in the context of established industrial companies. Building on the prior innovation literature, resource-based view, and dynamic capabilities view, we conduct a qualitative study of technological and marketing capabilities in relation to DDI. Based on interview data from six multinational B2B companies, we find that even though technological capabilities are vital to DDI, five of the six examined companies struggle more with marketing capabilities in developing DDI. The research findings underline the central role of customer understanding and involvement in DDI, as well as the significance of the ability to articulate the DDI value proposition in a form that potential customers can grasp. The study contributes to our understanding of DDI as a phenomenon in the context of established manufacturing companies, and identifies key challenges for intangible data-driven innovations in this context.